Canada. Significant achievements 2011 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2022)
The main activities carried out by the Institute in Canada during 2011 are identified, with respect to the needs and interests of the country, strengthening issues such as financing, security, insurance, genetics, research, use of information, trade, health and safety, technical assistance, genetically modified organisms, bioactive compounds, solid science and in the sheep value chain.